Kontribusi Pedagang Wanita Pasar Tradisional Dalam Meningkatkan Kesejahteraan Keluarga dalam Tinjauan Ekonomi Islam (Studi Kasus Pasar Lau Cih Medan) - Zakia, Maulida Ummi; Nasution, Yenni Samri Juliati; Nasution, Juliana (Jurnal Ilmiah Ekonomi Islam, 2024)
This study employs a descriptive qualitative research method. It was conducted directly on the subject, namely the female traders at the Lau Cih Central Market in Medan. Data was gathered through observation, interviews, and documentation, and then analyzed qualitatively using data reduction, data presentation, and data verification. The findings reveal that the contribution of female traders in the Lau Cih Central Market includes alleviating the financial burden on their families, acting as the breadwinners or heads of households, and helping to improve family finances. Despite these roles, they do not neglect their primary responsibilities as homemakers, balancing their time between work and family matters. From an Islamic economic perspective, a wife working is not in conflict with Islamic law, as a working wife is considered to be assisting her husband in providing income, which is seen as a form of devotion in supporting the family. The factors motivating a wife to work include economic necessity, social factors, and self-actualization.